Analisa Perkawinan Beda Agama di Indonesia - Moody Rizqy Syailendra; Michelle Sharon Anastasia; Fauzan Ravinda Putera (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Marriage is an inner birth network between a man and a woman as husband and wife, with the primary purpose of creating a happy family based on the same Divinity. A mixed marriage is generally defined as a marriage between two people in Indonesia who are subject to opposing laws due to differences in nationality. A mixed marriage of different religions is a marriage carried out by a man and a woman who have different beliefs; this, if associated with Islamic law, is not permitted and considered deviant, not only under Islamic laws but also under the law on marriage and the law about marriage prohibition. Keywords: Marriage, mixed marriage, marriage of different religions